eGFP-tagged Wnt-3a enables functional analysis of Wnt trafficking and signaling and kinetic assessment of Wnt binding to full-length Frizzled - Wesslowski, Janine; Kozielewicz, Pawel; Wang, Xianxian; Cui, Haijun; Schihada, Hannes; Kranz, Dominique; Karuna, Pradhipa M.; Levkin, Pavel; Gross, Julia Christina; Boutros, Michael; Schulte, Gunnar; Davidson, Gary (The journal of biological chemistry, 2020)
The Wingless/Int1 (Wnt) signaling system plays multiple, essential roles in embryonic development, tissue homeostasis, and human diseases. Although many of the underlying signaling mechanisms are becoming clearer, the binding mode, kinetics, and selectivity of 19 mammalian WNTs to their receptors of the class Frizzled (FZD(1?10)) remain obscure. Attempts to investigate Wnt-FZD interactions are hampered by the difficulties in working with Wnt proteins and their recalcitrance to epitope tagging. Here, we used a fluorescently tagged version of mouse Wnt-3a for studying Wnt-FZD interactions. We observed that the enhanced GFP (eGFP)-tagged Wnt-3a maintains properties akin to wild-type (WT) Wnt-3a in several biologically relevant contexts. The eGFP-tagged Wnt-3a was secreted in an evenness interrupted (EVI)/Wntless-dependent manner, activated Wnt/?-catenin signaling in 2D and 3D cell culture experiments, promoted axis duplication inXenopusembryos, stimulated low-density lipoprotein receptor-related protein 6 (LRP6) phosphorylation in cells, and associated with exosomes. Further, we used conditioned medium containing eGFP-Wnt-3a to visualize its binding to FZD and to quantify Wnt-FZD interactions in real time in live cells, utilizing a recently established NanoBRET-based ligand binding assay. In summary, the development of a biologically active, fluorescent Wnt-3a reported here opens up the technical possibilities to unravel the intricate biology of Wnt signaling and Wnt-receptor selectivity.